Osteochondroma of the cervical spine - Karakaş, Eyüp S.; Patıroğlu, Tahir E. (The Turkish Journal of Pediatrics, 1986)
The case of a seven-year-old boy with solitary osteochondroma originating in the spinous process of the cervical spine, which is a rare condition, is presented.
Keywords: cervical spine; osteochondroma